2022
DOI: 10.3390/medicina58121779
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight, Body Composition, Phase Angle, and Resting Metabolic Rate in Male Patients with Stage IV Non-Small-Cell Lung Cancer Undergoing Therapy

Abstract: Background and Objectives: Cancer treatments can adversely influence body weight status, body composition, phase angle (PhA), and resting metabolic rate (RMR), which could possibly affect disease course. Τhe aim was to assess differences in body composition, PhA, RMR, and related parameters in non-small-cell lung cancer (NSCLC) patients after treatment. Methods: The sample consisted of 82 NSCLC (stage IV) male patients (chemotherapy (C) 15.7%; immunotherapy (I) 13.3%; C + I 25.3%; (C) + radiotherapy (R) 22.9 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, several variables that influence MPV, such as genetic polymorphisms, body composition, and diet, were not assessed, and these may affect both cancer prognosis [ 129 ] and platelet secretory molecules [ 130 , 131 , 132 ]. In addition, usual treatments may also induce changes in biological parameters [ 133 ]. Last but not least, cancer patients often take vitamins and oral nutritional supplements to cover their nutritional needs, which most often contain fat to increase caloric supply [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several variables that influence MPV, such as genetic polymorphisms, body composition, and diet, were not assessed, and these may affect both cancer prognosis [ 129 ] and platelet secretory molecules [ 130 , 131 , 132 ]. In addition, usual treatments may also induce changes in biological parameters [ 133 ]. Last but not least, cancer patients often take vitamins and oral nutritional supplements to cover their nutritional needs, which most often contain fat to increase caloric supply [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Detopoulou et al [ 40 ] were found significant correlations between PhA and FFM (rho = 0.247; p = 0.02), but no significant correlation for waist and hip circumference (cm), waist-hip ratio, body fat (%), BCM (Kg), total body water (TBW), extra-cellular and intra-cellular water (ECW, ICW). In the other study, Spearman’s correlation shows no significance between PhA, anthropometric and BC variables [ 41 ]. In Wei Ji et al [ 36 ], in addition to PhA, other variables were also examined, such as appendicular skeletal muscle mass (ASMM), BMI and skeletal muscle mass index (SMI).…”
Section: Resultsmentioning
confidence: 88%
“…Three studies included patients not undergoing CHT, RT and without specific treatment information [ 37 , 39 , 45 ] while newly diagnosed patients and/or patients with ongoing therapies were evaluated in remaining studies [ 34 , 36 , 38 , 42 ]. Suzuki et al [ 43 ] evaluated LC patients after surgery while patients were evaluated after cancer treatment in two studies [ 40 , 41 ]. Castanho et al [ 44 ] evaluated patients after surgery and after cancer treatment (CHT, RT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation